Evolution of NLR Resistance Genes in Magnoliids: Dramatic Expansions of CNLs and Multiple Losses of TNLs - Wu, Jia-Yi; Xue, Jia-Yu; Van de Peer, Yves (Frontiers in Plant Science, 2021)
Magnoliids is the third largest group of angiosperms and occupies a critical position in angiosperm evolution. In the past years, due to the lack of sequenced genomes, the disease resistance gene (R gene) profile of magnoliids remains poorly understood. By genome-wide identification of 1,832 NLR genes from seven magnoliids genomes, we built a framework for the evolution of magnoliids R genes. TNL genes were completely absent from five magnoliids, presumably due to immune pathway deficiencies. A total of 74 ancestral R gene lineages (70 CNLs, three TNLs and one RNL) were recovered in common ancestor of magnoliids, from which all current NLR gene repertoires were derived. Tandem duplication served as the major drive for NLR genes expansion in seven magnoliids genomes, as most surveyed angiosperms. Due to recent rapid expansions, most magnoliids exhibited “a first expansion followed by a slight contraction and a further stronger expansion” evolutionary pattern, while both L. cubeba and P. americana showed a twice-repeated pattern of “expansion followed by contraction”. Transcriptomes analysis of seven different tissues of S. chinensis revealed a low expression of most NLR genes, with the root and fruit R genes displaying a relatively higher expression. Overall, our study sheds light on the evolution of NLR genes in magnoliids, compensates for insufficiency in major angiosperm lineages, and provides an important reference for a better understanding of angiosperm NLR genes.